A unique role for the Rb protein in controlling E2F accumulation during cell growth and differentiation. - Ikeda, M A (1996)
Examination of the interactions involving transcription factor E2F activity during cell growth and terminal differentiation suggests distinct roles for Rb family members in the regulation of E2F accumulation. The major species of E2F in quiescent cells is a complex containing the E2F4 product in association with the Rb-related p130 protein. As cells enter the cell cycle, this complex disappears, and there is a concomitant accumulation of free E2F activity of which E2F4 is a major component. E2F4 then associates with the Rb-related p107 protein as cells enter S phase. Rb can be found in interactions with each E2F species, including E2F4, during G1, but there appears to be a limited amount of Rb with respect to E2F, likely due to the maintenance of most Rb protein in an inactive state by phosphorylation. A contrasting circumstance can be found during the induction of HL60 cell differentiation. As these cells exit the cell cycle, active Rb protein appears to exceed E2F, as there is a marked accumulation of E2F-Rb interactions, involving all E2F species, including E2F4, which is paralleled by the conversion of Rb from a hyperphosphorylated state to a hypophosphorylated state. These results suggest that the specific ability of Rb protein to interact with each E2F species, dependent on concentration of active Rb relative to accumulation of E2F, may be critical in cell-growth decisions.